Antisolvent‐assisted Crystallization of Centimeter‐sized Lead‐free Bismuth Bromide Hybrid Perovskite Single Crystals with X‐ray Sensitive Merits. Issue 24 (10th November 2021) - Xu, Yaxin; Hu, Jiarui; Du, Xinyuan; Xiao, Xinglin; Li, Mingkai; Tang, Jiang; Chen, Junnian; He, Yunbin
Abstract: Hybrid bismuth halides perovskites have emerged as promising candidates for X‐ray detection, due to the strong absorptivity of high‐energy X‐ray photons, high resistivity, large carrier diffusion length and low toxicity. However, the mostly investigated hybrid bismuth iodides single crystals are usually opaque and require a harsh synthesis process. Herein, novel one‐dimensional (1D) pentamethylenediamine bismuth bromide (PDA)BiBr5 single crystals were synthesized via an antisolvent‐assisted crystallization method at room temperature. Bulk (PDA)BiBr5 single crystals have sizes of 10×1.3×1.5 mm 3 and high transparency. They are shown to have low density of defects of 2.0×10 10 cm −3 and obvious photoconductivity. Moreover, they exhibit large bulk resistivity of 2.13×10 11 Ω cm and good X‐ray attenuation coefficient. Consequently, the vertical structured (PDA)BiBr5 single crystal X‐ray photoconductor produces a sensitivity of 3.8 μC Gyair −1 cm −2 . This study provides a facile strategy for synthesizing bulk hybrid bismuth bromides single crystals with potential X‐ray detection application. Abstract : A novel hybrid bismuth bromide perovskite with centimeter size and high transparency was synthesized via antisolvent‐assisted crystallization, exhibiting promising X‐ray detection behavior.